The Role of Education in Increasing Public Awareness of Dental and Oral Health - Handayani, Ni Luh; Hidayat, Dasrun; Handayani, Nining (ProBisnis : Jurnal Manajemen, 2025)
The level of public awareness of dental and oral health in Indonesia is still relatively low, as indicated by the high prevalence of dental disorders and minimal access to dental health services. This study aims to explore the role of education in increasing public awareness of the importance of dental and oral care. The study used a mixed methods approach with an exploratory sequential design, starting from a qualitative study through in-depth interviews with 10 informants, then continued with a quantitative survey of 60 respondents in the Bonebobakal Health Center work area, Central Sulawesi. The results showed that education delivered by health workers, especially through direct counseling and visual media such as leaflets and videos, was able to increase public knowledge and awareness. However, behavioral changes have not yet occurred evenly. The SEM-PLS model shows that the effectiveness of education is not only influenced by the delivery of information, but also by active community participation. The main obstacles found include the lack of continuity of counseling, limited coverage, and cultural factors and fear of medical procedures. Contextual education, involving local cadres, and utilizing digital media can increase the effectiveness of delivering health messages. These findings emphasize the importance of integrating dental and oral education into the integrated health post program and strengthening the communication capacity of health workers to bridge the gap between knowledge and practice. This study recommends the development of sustainable and community-based educational strategies to improve the quality of life of the community as a whole.